2021
DOI: 10.3390/antiox10071080
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Silica Liquid Protects Pancreatic β Cells from Streptozotocin-Induced Oxidative Damage

Abstract: Type 2 diabetes mellitus is a complex multifactorial disease characterized by insulin resistance and dysfunction of pancreatic β-cells. Rice husk silica liquid (RHSL) is derived from rice husks and has not been explored in diabetes mellitus until now. Previous studies showed that rice husk is enriched with silica, and its silica nanoparticles are higher more biocompatible. To investigate the potential protective role of RHSL on pancreatic β cells, we utilized RIN-m5F pancreatic β cells and explored RHSL effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Excessive ROS can cause a decrease in the activity of INS-1 cells, ultimately leading to cell necrosis and apoptosis [ 28 , 29 ]. Insulin resistance is also related to oxidative-stress-induced dysfunction in type 2 diabetes [ 5 ]. In this experiment, we treated INS-1 cells with hydrogen peroxide, hA or high concentration of glucose to change ROS levels and establish an insulin resistance model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive ROS can cause a decrease in the activity of INS-1 cells, ultimately leading to cell necrosis and apoptosis [ 28 , 29 ]. Insulin resistance is also related to oxidative-stress-induced dysfunction in type 2 diabetes [ 5 ]. In this experiment, we treated INS-1 cells with hydrogen peroxide, hA or high concentration of glucose to change ROS levels and establish an insulin resistance model.…”
Section: Discussionmentioning
confidence: 99%
“…As many factors cause T2DM, its pathogenesis remains unclear [ 4 ]. Insulin resistance (IR) and islet β-cell failure are the key pathogenic factors of T2DM [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of blood glucose depends on the release of insulin. In our previous study, we showed that RHSL abrogated the effect of streptozotocin (STZ) on the mass of RIN-m5F pancreatic β-cells and their ability to secrete insulin [ 16 ]. In the present study, we observed similar results, where RHSL restored blood insulin concentrations, meaning that RHSL has the potential to reverse the STZ-induced insulin resistance in C57BL/J6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed process of rice husk preparation can be found in previous studies [ 18 ]. In addition, the production process and the conditions of aqueous RHSL (rice-husk silica liquid) were performed according to our previous research [ 16 ]. The produced standard solution was used at the original concentration and diluted with double-distilled water (ddH 2 O) to obtain an effective dose, which was used in the subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation